Massive health education through technological mediation: Analyses and impacts on the syphilis epidemic in Brazil - Caitano, Alexandre R.; Gusmão, Cristine M. G.; Dias-Trindade, Sara; Barbalho, Ingridy M. P.; Morais, Philippi Sedir G.; Caldeira-Silva, Gleyson J. P.; Romão, Manoel H.; Valentim, Janaína L. R. S.; Dias, Aline P.; Alcoforado, Joaquim L. M.; Oliveira, Carlos A. P.; Coutinho, Karilany D.; et al. (Frontiers in Public Health, 2022)
With syphilis cases on the rise, Brazil declared an epidemic in 2016. To address the consequent public health crisis, the Ministry of Health laid out a rapid response plan, namely, the “Syphilis No!” Project (SNP), a national instrument to fight the disease which encompasses four dimensions: (a) management and governance, (b) surveillance, (c) comprehensive care, and (d) strengthening of educommunication. In the dimension of education, the SNP developed the learning pathway “Syphilis and other Sexually Transmitted Infections (STIs)” to strengthen and promote Health Education. This pathway features 54 Massive Open Online Courses (MOOCs), delivered through the Virtual Learning Environment of the Brazilian Health System (AVASUS). This paper analyzes the impacts of the learning pathway “Syphilis and other STIs” on the response to the epidemic in Brazil, highlighting the educational process of the learning pathway and its social implications from the perspective of the United Nations' 2030 Agenda and its Sustainable Development Goals. Three distinct databases were used to organize the educational data: the learning pathway “Syphilis and other STIs” from AVASUS, the National Registry of HealthCare Facilities from the Brazilian Ministry of Health (MoH), and the Brazilian Occupation Classification, from the Ministry of Labor. The analysis provides a comprehensive description of the 54 courses of the learning pathway, which has 177,732 enrollments and 93,617 participants from all Brazilian regions, especially the Southeast, which accounts for the highest number of enrollees. Additionally, it is worth noting that students living abroad also enrolled in the courses. Data characterization provided a demographic study focused on the course participants' profession and level of care practiced, revealing that the majority (85%) worked in primary and secondary healthcare. These practitioners are the target audience of the learning pathway and, accordingly, are part of the personnel directly engaged in healthcare services that fight the syphilis epidemic in Brazil.